Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.paid.2021.110892
|View full text |Cite
|
Sign up to set email alerts
|

Political polarization on COVID-19 pandemic response in the United States

Abstract: Despite calls for political consensus, there is growing evidence that the public response to the COVID-19 pandemic has been politicized in the US. We examined the extent to which this polarization exists among the US public across two national studies. In a representative US sample ( N = 699, March 2020) we find that liberals (compared to conservatives) perceive higher risk, place less trust in politicians to handle the pandemic, are more trusting of medical experts such as the WHO, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
211
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(238 citation statements)
references
References 67 publications
16
211
2
9
Order By: Relevance
“…This pattern was evident for perceptions of COVID-19 risk and behavior change intentions as well. Kerr et al (2021) investigated the extent of the polarization among the US public across two national studies. The first study conducted in March showed that liberals (compared with conservatives) perceived higher risk, exhibited less trust in politicians to effectively handle the pandemic and more trust of medical experts, such as the WHO, and reported engaging in more health-protective actions.…”
Section: Motivated Reasoning-a Case For Politicization Of the Crisismentioning
confidence: 99%
“…This pattern was evident for perceptions of COVID-19 risk and behavior change intentions as well. Kerr et al (2021) investigated the extent of the polarization among the US public across two national studies. The first study conducted in March showed that liberals (compared with conservatives) perceived higher risk, exhibited less trust in politicians to effectively handle the pandemic and more trust of medical experts, such as the WHO, and reported engaging in more health-protective actions.…”
Section: Motivated Reasoning-a Case For Politicization Of the Crisismentioning
confidence: 99%
“…COVID-19 emerged as a pandemic in the first quarter of the year 2020 and had social ( Yezli and Khan, 2020 ), ecological ( Muhammad et al, 2020 ), political ( Kerr et al, 2021 ), and economic ( Qian et al, 2021 ) effects all over the world. At present, no internationally recognized measures are used as standards to cure COVID-19 patients ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For exploratory purposes, we assessed potential heterogeneity in the receptivity to our messages along political ideological orientation as preferences for public health measures, including vaccination has been shown to differ along political ideology (31)(32)(33). We interacted the pooled treatment indicator with self-reported political ideological orientation (conservative, moderate, or liberal, see Table S11 in SI Appendix).…”
Section: Resultsmentioning
confidence: 99%
“…Preferences for public health measures, including vaccination differ along political ideology (31)(32)(33), and the gap between COVID-19 vaccination rates in blue and red states have continued to grow (5). It is therefore also particularly noteworthy that our messages work well among individuals identifying as political moderates and conservatives.…”
Section: Discussionmentioning
confidence: 99%